PENEGAKAN HUKUM KEPADA PENYANYI COVER DI YOUTUBE BERDASARKAN UNDANG-UNDANG HAK CIPTA - Ramadhana, Bramantyo Hutomo; Rosando, Abraham Ferry (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
This..paper is intended to study and research related. to how to enforce the law against cover singers on the Youtube platform, because basically this activity will invite various opinions related to someone’s copyright. In the discussion of this research, the author will use the type of normativ...Legaal. .reesearch. Normative legal reesearch is legal research to..find thee..Ruleof law, legalprinciples,and legaldoctrines in order to answerthe legalissue faced, normativelegal ressearch is carried out to fin,d solutions to existing legal issues. The results of several existing studies explain that one of the events found on online platforms, especially Youtube, is the frequent occurrence of violations related to song copyrights committed by Cover content creators, in this case republishing the copyrighted works of people as songwriters and.not awarre..of the iimportance..of the..ecconomic rights.and mo,ral..rightsof..th,e songwriter. From this incident, it..canbe..conclu,ded that.there is..no awareness and strict regulations regarding copyright of songs sung again on several online platforms, especially Youtube and also the importance of specific government regulations in the use of song copyrighted works on online platforms